Somatosensory discrimination intervention improves body position sense and motor performance in children with hemiplegic cerebral palsy - McLean, B.; Taylor, S.; Blair, E.; Valentine, J.; Carey, L.; Elliott, Catherine (American Occupational Therapy Association, Inc., 2017)
Objective: This study examined the use of the adult neuroscience-based Sense© intervention with children with hemiplegic cerebral palsy (HCP) to improve upper-limb somatosensory discrimination, motor function, and goal performance. Method: Seventeen children with HCP (9 boys, 8 girls; mean age = 10.2 yr) participated in this pilot matched-pairs trial with random allocation and 6-mo follow-up (intervention, n = 7; control, n = 10). The intervention group received Sense training 3×/wk for 6 wk (18 hr). Outcome measures included Goal Attainment Scaling, Sense-assess© Kids, and the Assisting Hand Assessment. Results: The intervention group improved in goal performance, proprioception, and bimanual hand use and maintained improvement at 6-mo follow-up. The control group improved in occupational performance by 6-mo follow-up. CONCLUSION: This study established the feasibility of using the Sense intervention in a pediatric setting and adds preliminary evidence to suggest that improving somatosensory function can improve motor function and goal performance among children with HCP.